Manufacturing technology for contacts to silicon carbide - Kudryk, Ya. Ya.; Bigun, R. I.; Kudryk, R. Ya. (Technology and design in electronic equipment, 2013)
The authors classified the results of investigations of resistivity of ohmic contacts to silicon carbide made without any semiconductor surface modification. A set of contacts with better parameters were analysed. From the results of this analysis, some recommendations were made concerning optimal contact-forming layers for p- and n-SiC types of 4H, 6H, 3C, 15R, 21R polytypes.